Global research trends and hotspots of fecal microbiota transplantation: A bibliometric and visualization study - Wang, Mancai; Xie, Xiaofeng; Zhao, Songbo; Han, Wei; Zhang, Youcheng (Frontiers in Microbiology, 2022)
Introduction Fecal microbiota transplantation (FMT) has gained considerable attention in a variety of clinical research areas, and an increasing number of articles are being published. It is very critical to reveal the global status, future research trends, and hotspots in the FMT research and application. Methods We searched the Web of Science Core Collection up to May 10, 2022, and only articles and review articles about FMT were included finally. CiteSpace 5.8.R3, VOSviewer 1.6.18, Scimago Graphica and Microsoft Office Excel 2019 were used for data analysis and visualization. The results included publication characteristics, Co-authorships analysis, Co-cited analysis, Co-occurrence analysis, and burst analysis. Results 11972 records were used for the analysis and visualization finally, these records were published between 1980 and 2022, and the publication about FMT is increasing year by year. Co-authorship analysis shown that the USA played a key role in this field. After data analysis and visualization, a total of 57 hotspots about FMT were produced. We summarized these hotspots and classified them into 7 grades according to the number of evidence sources. The evidence sources included top 25 of Web of Science categories, top 30 most Co-cited references, top 10 clusters of references, top 25 references with the strongest citation bursts, top 25 keywords with the most occurrence frequency, major 15 clusters of keywords, top 25 keywords with the strongest citation bursts, and top 30 disease keywords. Conclusion This bibliometric analysis is expected to provide overall perspective for FMT. FMT has gained increasing attention and interest, there are many hotspots in this field, which may help researchers to explore new directions for future research.